CURRENT TRENDS AND UNPREDICTABLE CHALLENGES OF AN EMERGENCY ABDOMINAL SURGERY IN UKRAINE - Slonetsky, B.I.; Tutchenko, N.I.; Verbitsky1, I.V.; Kotsiubenko, V.O. (World of Medicine and Biology, 2020)
The purpose of the study was to present the results of a comparative analysis of emergency abdominal surgery in Ukraine between 2000 and 2019 and to identify significant dynamic negative and debatable trends that need further reconsideration in order to improve the provision of emergency abdominal surgery. Over the past 20 years, the number of surgeons, including doctors at the research and training institutions of the Ministry of Health of Ukraine has decreased from 8,990 to 7,218 (-19.72%), the employment of full-time positions decreased significantly from 97.4% to 89.79%, the total number of surgical interventions on the digestive organs and abdominal cavity decreased from 344,732 operations to 274,196 (-20.47%), and the number of emergency surgeries decreased accordingly from 261,732 operations to 160,937 (-38.51%) operations. In addition, a third of surgical specialists are doctors of retirement and nearing retirement age, and among retired surgeons who do not leave the practice, 34.4% are of past retirement age (over 70 years).